Antimicrobial Activity of Lemon and Peppermint Essential oil in Edible Coating Containing Chitosan and Pectin on Rainbow Trout (Oncorhynchus mykiss) Fillets - Leila Tabatabaei Moradi; Anousheh Sharifan; Kambiz Larijani (Pasteur Institute of Iran, 2015)
Introduction: Essential oils are used as flavoring agents in various foods. Layer-by-Layer (LBL) technique is a method in which the material is dipped into a series of different solutions containing oppositely charged polyelectrolytes. The aim of this study is to investigate the effectiveness of a multilayered edible coating with an antimicrobial compound (Lemon and Peppermint) in enhancing the quality and shelf-life of rainbow trout (Oncorhynchus mykiss) during refrigerated storage (4 ± 1˚C) over a period of 16 days. Methods: In this study, multilayered coating was used with two concentrations of Lemon (LEO) and Peppermint (PEO) essential oils (0.5 and 1%). Antibacterial effect of these treatments was evaluated by enumeration of bacteria in special culture media. The control and the coated fish samples were analyzed periodically for pH and microbiological (total viable count, psychrotrophic count, lactic acid bacteria, Enterobacteriaceae, and coliform) characteristics. Results: The results obtained in this study demonstrate that multilayered coating in combination with Lemon and Peppermint essential oils can significantly decrease the number of bacteria and delay the spoilage of the samples (p<0.05). Conclusion: Multilayered edible coating with an antimicrobial compound can properly delay the growth of spoilage microorganisms and prolong the shelf life of meat products.